How Threats of Exclusion Mobilize Palestinian Political Participation - A Response to Bochkareva, Silagadze and Stephan - - Chagai M. Weiss; Alexandra Siegel; David Romney (Institute for Replication (I4R), 2025)
In our article, "How Threats of Exclusion Mobilize Palestinian Political Participation," we argue that threats of exclusionary policies can mobilize minority citizens through both electoral and non-electoral channels. Using Donald Trump's 2020 "Deal of the Century" (DOC)- which explicitly threatened the citizenship status of a subset of Palestinian citizens of Israel in the Triangle area-we show that the announcement increased political discourse on Facebook, voter turnout, and registrations to a Jewish-Arab social movement. Bochkareva, Silagadze and Stephan (2025) replicate our analyses and reproduce our main findings. They raise thoughtful concerns about the parallel trends assumption, and robustness to alternative treatment definitions and outcome measures. While we welcome these contributions, we clarify that our core design choices-including focusing our analysis on three recurring elections in 2019-2020, and ten localities mentioned in the DOC-were substantively motivated and pre-registered. Building on Bochkareva, Silagadze and Stephan (2025), and drawing on our substantively justified research design, we employ additional event studies that provide further support for the observable implications of the parallel trends assumption, as well as our theoretical argument that threats of exclusion can mobilize minority political participation. We also address data sharing limitations stemming from platform terms of service, data agreements, and ethical concerns, and explain our matching procedures. We conclude by commending the authors' decomposition of mobilization patterns and agree that variation between institutionalized and non-institutionalized responses presents a promising avenue for future research.
https://doi.org/10.7910/DVN/EGXUBU
Keywords: 330